Tandem structured spectrally selective coating layer of copper oxide nanowires combined with cobalt oxide nanoparticles. (January 2015) - Kim, Tae Kyoung; VanSaders, Bryan; Moon, Jaeyun; Kim, Taewoo; Liu, Chin-Hung; Khamwannah, Jirapon; Chun, Dongwon; Choi, Duyoung; Kargar, Alireza; Chen, Renkun; Liu, Zhaowei; Jin, Sungho
Abstract: Increasing the light absorption across the wide solar spectrum has important implications for applications in solar-thermal and photovoltaic energy conversion. Here, we report novel tandem structures combing two different materials with complementary optical properties and microstructures: copper oxide (CuO) nanowires (NWs) and cobalt oxide (Co3 O4 ) nanoparticles (NPs). Copper oxide NWs of 100–200 nm in diameter and 5 µm long are grown thermally on copper foil in air and cobalt oxide NPs of 100–200 nm in diameter are synthesized hydrothermally. Tandem structures of spectrally selective coating (SSC) layer are built with three different methods: spray-coating, dip-coating of cobalt oxide NPs into copper oxide NWs forest, and transferring of copper oxide NWs layer onto cobalt oxide NPs layer. The tandem-structured SSC layers fabricated from the spray-coating, dip-coating and transferring methods exhibit figure of merit (FOM) values of 0.875, 0.892 and 0.886, respectively, which are significantly higher than that of the starting copper oxide NWs (FOM=0.858) and cobalt oxide NPs (FOM=0.853). Our results demonstrate the efficacy of using novel tandem structures for enhanced light absorption of solar spectrum, which will find broad applications in solar energy conversion. Graphical abstract: Highlights: Tandem structured SSC layers are devised with CuO NWs and Co3 O4 NPs. Scalable wet-coating procedure is applied to make this SSC layers. Improved absorption in both visible and near-IR spectrum is achieved to have FOM of 0.892.